Cult and Koinon in Hellenistic Thessaly - Graninger, Denver. (Brill Studies in Greek and Roman Epigraphy, 2011)
Cult and Koinon in Hellenistic Thessaly examines the territorial expansion of the Thessalian League circa 196-27 BCE and the development of the state religion of the League. Individual chapters trace the adoption of a common Thessalian calendar by new members of the League, the establishment of new regional festivals, the elaboration or reorganization of older cults, and League participation in a network of international festivals; cult could equally well enact alternatives to this political arrangement, however, and older religious traditions continued to be maintained both within new League territories and especially at Delphi. The result is a fresh portrait of the politics of cult on the Greek mainland in the later Hellenistic period.